KEBUTUHAN LAYANAN AIR BERSIH PADA MASYARAKAT DI DESA KEDI KECAMATAN LOLODA KABUPATEN HALMAHERA BARAT - Yuner Harimisa; Ferdinand Kerebungu; Abdul Rasyid Umaternate (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
This research aims to find out how the perception of the people of Kedi Village towards the needs of clean water services and to find out why there is no direct conflict between the people of Kedi Atas and the people of Kedi Bawa (Medo RT 1) in meeting the needs of clean water, this research was conducted in Kedi Village, South Loloda District, West Halmahera Regency. The research method used is qualitative research by collecting observation data and in-person interviews with several informants. The results of research in general show that clean water is the most important and important need for the people of Kedi Village but the people of Kedi Atas are very difficult to access clean water and still rent vehicles and power to get water. while the people of Kedi Bawa (Medo RT 1) are very easy to get clean water. The people of Kedi Atas and Kedi Bawa do not conflict directly in meeting the needs of clean water located in Kedi Bawa because there are factors that become binders in the social life of the people of Kedi Village, namely family between kedi Atas and Kedi Bawa people working together and please help if there are families who experience shortages.